Raising the efficiency of drip irrigation by using mulch for Tomato in protected agriculture (Damascus University Journal of agriculture sciences, 2024)
The research was carried out at Alsanobar Research Station – Lattakia – General Commission for Scientific Agricultural Research. During the  two seasons 2020–2021 to determine the effect of two different irrigation methods on the consumption of the tomato crop (Lycopersicom esculentum) and some studied indicators.Two irrigation treatments (Open drip irrigation, Covered drip irrigation) in Three  replications  by  using  full  random  sectors.The water consumption of the crop was calculated and the effect of irrigation method on (productivity, plant height, maximum flowering date) was studied.The total water consumption was determined as 3872 m3/ha for the open drip irrigation treatment, and 3407.34 m3/ha for the covered drip irrigation treatment by saving 12% of the water provided in the open drip irrigation treatment.Covered drip irrigation was superior in terms of plant height, early flowering, and the average productivity of the greenhouse 3.16 tons/house by 16.2%, compared with open drip irrigation.
Keywords: Surface Irrigation; Drip Irrigation; Tomatoes; Productivity; Water Consumption.